Use of the silicone elastomer-dacron ureteral prosthesis in neoplastic ureteral obstructions - Corio, Ernesto; Clark, Omar; Campalans, Luis; Pollero, Héctor (Cirugía del Uruguay, 1976)
In two patients with neoplastic uretheral obstruction, a silicon-dacron elastomere prosthesis of original design was used to salve the situation. In both cases there was a normalization of urinary flow far periods of one and four months. It is considered that, together with antineoplastic therapy, the procedure is useful as a palliative in selected cases.